Synthesis and Characterized of Some 3-Amino-Alkyl/Aryl-3,4Dihydr-4-Oxoquinazolines and Their Acyl Derivateives - Srivastava, M.K.; Rukhaiyar, Arvind; Trivedi, K.M. (Asian Journal of Chemistry, 2010)
In the present paper we describe the synthesis and characterisation of some 3-amino-2-alkyl/aryl-3,4-dihydro-4-oxoquinazoline (I-VI). Various acyl derivatives of these 4-oxoquinazolines (VII, VIII) were prepared and their structure established by various physico-chemical methods.